Adult hypophosphatasia presenting with recurrent acute joint pain - Hayao Yoshida; Takaaki Murakami; Atsubumi Ogawa; Takashi Sunouchi; Naoko Hidaka; Nobuaki Ito; Hiromi Murakami; Hidenori Kawasaki; Tomoyuki Akiyama; Katsumi Nakajima; Daisuke Yabe; Taizo Yamamoto (Endocrinology, Diabetes & Metabolism Case Reports)
Hypophosphatasia (HPP) is a genetic disorder due to pathological variants in ALPL, the gene encoding tissue-nonspecific alkaline phosphatase (ALP). HPP is typically associated with bone-related symptoms, such as bone deformity, fractures and bone pain in children, but can appear in adults with symptoms resembling arthritis. A 22-year-old male experienced repeated and severe sudden attacks of joint pain in the elbows and knees. Magnetic resonance imaging and joint ultrasonography showed joint effusions indicating chronic inflammation. Blood biochemical tests revealed a remarkably low serum ALP level, and repeated examination confirmed a sustained low ALP level; urine phosphoethanolamine, plasma inorganic pyrophosphate and plasma pyridoxal-5′-phosphate levels were elevated, raising concern for HPP. While the patient had no history of premature loss of primary teeth, fragility fractures, muscle weakness or abnormalities in growth, genetic testing revealed a likely pathogenic and a pathogenic heterozygous variant in the ALPL gene, i.e., c.979T>C (p.Phe327Leu) and c.1559del (p.Leu520Argfs), confirming HPP. Additional genetic testing of his parents showed a heterozygous c.1559del variant in his father and a heterozygous c.979T>C variant in his mother. A diagnosis of adult HPP due to compound heterozygous mutations was therefore confirmed. Enzyme replacement therapy with asfotase alfa was then introduced; no attacks of arthralgia occurred in the 1-year period since then. This case highlights the possibility of HPP in adults who present clinically with repeated joint symptoms and low serum ALP levels but without bone-related symptoms.